Strategi Kesbangpol Aceh Dalam Meningkatkan Partisipasi Pemilih Pemula - Arsyi Arsyi; Rahmad Rahmad (Journal of Social and Policy Issues, 2022)
The focus of the discussion of this study is how the strategy of the National Unity and Politics Agency in providing political education based on existing problems by increasing public awareness, especially among beginner voters in the 2024 election participation. Running well or not in the implementation of political education. This research method uses exploratory research with a literature study approach. The data collection technique used by researchers in this study is secondary data. The political education program for novice voters in Aceh Province has been implemented properly. However, this activity was hampered due to the impact of the Covid-19 pandemic, so the re-focusing of the budget resulted in various programs not running properly.